2016
DOI: 10.1542/peds.2015-3425
|View full text |Cite
|
Sign up to set email alerts
|

Poor Parental Sleep and the Reported Sleep Quality of Their Children

Abstract: BACKGROUND: Pediatric sleep disturbances are regularly diagnosed on the basis of parental reports. However, the impact of parental sleeping problems on parental perceptions and reports of their child's sleep has not yet been studied. We hypothesized that poor parental sleep decreases the parent-reported child sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 28 publications
(28 reference statements)
4
41
1
Order By: Relevance
“…A methodological issue that could account for the association between parental insomnia and parent reports of children's sleep difficulties in particular, is that parental insomnia may affect their perception of children's sleep without any real underlying sleep problem of the child [24]. This can be important because parents are often the first to perceive their children's sleep problems and to seek help.…”
Section: Introductionmentioning
confidence: 99%
“…A methodological issue that could account for the association between parental insomnia and parent reports of children's sleep difficulties in particular, is that parental insomnia may affect their perception of children's sleep without any real underlying sleep problem of the child [24]. This can be important because parents are often the first to perceive their children's sleep problems and to seek help.…”
Section: Introductionmentioning
confidence: 99%
“…Parents rate the frequency of a specific behaviour during the past month using a four-point scale, ranging between 0 for "Never" and 3 for "Very Often". The quality of parental sleep can be a potential predictor for poor postoperative sleep quality in children, where parents who sleep poorly tend to overestimate sleeping problems in their children (Ronnlund et al, 2016). As an attempt to control for confounding effects, the PSQI was administered to collect information pertaining to parental sleep quality.…”
Section: Conners Behaviour Rating Scalesmentioning
confidence: 99%
“…As a result, a social desirability bias may influence parents to report a total sleep time that is higher compared to the observed total sleep time. Parents with poor sleep can also misreport their child's sleep (Ronnlund et al, 2016). Thus, using parent-reported assessments for their child's sleep can be insufficient, and actigraphy is required to provide additional information about a child's sleep patterns.…”
Section: Main Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…hypertension and type 2 diabetes (Redeker, 2011, Liu et al, 2013. A recent study showed that parents reporting sleep difficulties of their own may also overestimate sleep problems in their children (Rönnlund et al, 2016). The conclusion in that study was that future diagnostic methods and treatments in the field of pediatric sleep disorders, should not only take the child into consideration, but the whole family, including the parents.…”
Section: Parents Are Sleep-deprived Before the Child's Admissionmentioning
confidence: 96%